Cisco Unity fundamentals - Morgan, Brian (Brian Edward); Gonzalez, Moises (Cisco Press fundamentals series., 2005)
"Cisco Unity Fundamentals provides design and administration goals for migrating from PBX to Cisco IP Telephony, as well as working in a mixed PBX/Cisco IP Telephony environment. You will learn about the transition from the traditional model, with separate architectures for voice-mail and e-mail systems, to supporting unified messaging: e-mail, voice, and fax messages delivered to a single inbox. You will also discover common troubleshooting solutions, such as performance monitoring and the importance of data collection for predicting future system requirements"--Resource description page.